2015
DOI: 10.1111/aas.12586
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of propofol on emergence agitation – a meta‐analysis of randomized controlled trials

Abstract: Future studies on the benefits of adjunct propofol in reducing the incidence of EA are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…[ 5 ] Two meta-analyses have shown that administration of propofol in the dose range of 1–3 mg/kg was effective in reducing the incidence and severity of EA in children without affecting recovery time and time of care in the PACU. [ 2 3 ] Results from the present study indicate that a lower dose of 0.5 mg/kg of propofol exhibits a similar response in reducing the incidence of EA.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[ 5 ] Two meta-analyses have shown that administration of propofol in the dose range of 1–3 mg/kg was effective in reducing the incidence and severity of EA in children without affecting recovery time and time of care in the PACU. [ 2 3 ] Results from the present study indicate that a lower dose of 0.5 mg/kg of propofol exhibits a similar response in reducing the incidence of EA.…”
Section: Discussionsupporting
confidence: 54%
“…The incidence of EA varies around 10% to 80%, with the highest incidence found in patients aged 2 to 5 years. [ 2 3 ] A previous study by Aktara showed that the incidence of EA in our population was 39.7%. [ 4 ] Although it is a temporary and self-limiting condition, EA potentially endangers patients and threatens patient safety.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…has not been definitively shown to be effective in decreasing ED after a volatile anaesthetic. 23 42 64 Although a recent meta-analysis demonstrated that intraoperative propofol (1-3 mg kg À1 ) decreased EA in children, there were multiple confounders (midazolam, paracetamol, ketorolac, thiopental, morphine, fentanyl, sevoflurane, desflurane, and painful and non-painful procedures) 65 which, in this author's opinion, make the interpretation of the benefits of intraoperative propofol inadmissible.…”
Section: Gabapentinmentioning
confidence: 99%
“…Therefore, the therapy for agitation prevention and novel antiagitation drug development are quite limited because of the poor understands. At this moment, the common therapy for emergence agitation is sedative drugs, such as midazolam, propofol and opioids in clinical setting (13)(14)(15)(16). However, combined with other general anesthetics in PA-CU could significantly increase general anesthetic risk and result in respiratory depression and prolonged recovery.…”
mentioning
confidence: 99%